Human lysosomal acid lipase inhibitor lalistat impairs Mycobacterium tuberculosis growth by targeting bacterial hydrolases12. Issue 9 (21st July 2016) - Lehmann, J.; Vomacka, J.; Esser, K.; Nodwell, M.; Kolbe, K.; Rämer, P.; Protzer, U.; Reiling, N.; Sieber, S. A.
Abstract : Lalistat inhibits growth of Mycobacterium tuberculosis in bacterial culture as well as in infected macrophages. Abstract : Lalistat inhibits growth of Mycobacterium tuberculosis in bacterial culture as well as in infected macrophages. Target identification by quantitative proteomics revealed a cluster of 20 hydrolytic proteins including members of the lipase family. Lipases are essential for M. tuberculosis fatty acid production and energy storage thus representing promising antibiotic targets.